THE CLOTHING APPARATUS AND THE SEPARATION BETWEEN BEING AND PRAXIS: THINKING ABOUT A POWER OF NOT-DOING (Cadernos de Ética e Filosofia Política, 2021)
The goal of this article is to discuss the vesture, starting from Giorgio Agamben’s theory. In the first part, the conception of potency (brought by the Italian philosopher from the aristotelian teaching) is exposed. Then, we present the Agamben’s verification about the breaking between the being and the praxis. Ensuing, the notions of device and oikonomia are examined, in order to make easy the path to analyze the specific device vesture-nudity, what we do next. So, we make some critical notes about that and we finish the work bringing the category of profanation. The text’s background is the fracture between life and its form, between being and its doing, and the necessity of to preserve the characteristic, by excellence, of the humanity: the potency of not.